A contribution to the genus Romattalus Tshernyshev, 2021 (Coleoptera, Malachiidae) - Tong, Junbo; Tshernyshev, Sergei E.; Liu, Haoyu; Yang, Yuxia (Zootaxa, 2022)
The genus Romattalus Tshernyshev, 2021 is recorded from China for the first time. A new species, Romattalus flavojubatus Tong & Yang, sp. nov., is described and illustrated from Xizang, China. This new species is the second member of Romattalus and differs from R. dudkoi Tshernyshev, 2021 by the male sexually dimorphic pronotum possessing tufts of long pendent yellow hairs on lateral sides, and the shape of aedeagus, which is subparallel-sided at basal 2/3 in ventral view, then progressively narrowed apically, while in R. dudkoi, pronotum mixed with brown and yellow hairs, and the aedeagus distinctly swollen in middle part and widest at apical 1/4 part.